Editorial - Capogna, Stefania (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
Community Notebooks. People, Education and Welfare in the 5.0 society represents the challenge that we, as observers and scholars of society, wanted to take on, in order to try to make a contribution to the reflection that the complexity of the current period requires. The desire to measure ourselves against this challenge has matured during the pandemic crisis: the first issue sees the light at a time when we are still in the midst of the social, health and economic drama. Never as in this period has the fragility of modern society become more evident than in the past. Since the Enlightenment, it has made a vow of faith to science and technology, first kneeling at the altar of economics and then at that of financial speculation, producing the paradoxical effects of wealth without redistribution, which is amply testified to in the scientific literature and in the measurement indicators commonly adopted in studies on social inequalities.